Enhanced Text-to-Image Synthesis With Self-Supervision - Yong Xuan Tan; Chin Poo Lee; Mai Neo; Kian Ming Lim; Jit Yan Lim (IEEE Access, 2023)
The task of Text-to-Image synthesis is a difficult challenge, especially when dealing with low-data regimes, where the number of training samples is limited. In order to address this challenge, the Self-Supervision Text-to-Image Generative Adversarial Networks (SS-TiGAN) has been proposed. The method employs a bi-level architecture, which allows for the use of self-supervision to increase the number of training samples by generating rotation variants. This, in turn, maximizes the diversity of the model representation and enables the exploration of high-level object information for more detailed image construction. In addition to the use of self-supervision, SS-TiGAN also investigates various techniques to address the stability issues that arise in Generative Adversarial Networks. By implementing these techniques, the proposed SS-TiGAN has achieved a new state-of-the-art performance on two benchmark datasets, Oxford-102 and CUB. These results demonstrate the effectiveness of the SS-TiGAN method in synthesizing high-quality, realistic images from text descriptions under low-data regimes.